A New Physical Parameter Identification Method for Two-Axis On-Road Vehicles: Simulation and Experiment - Minyi Zheng; Peng Peng; Bangji Zhang; Nong Zhang; Lifu Wang; Yuanchang Chen (Shock and Vibration)
A new physical parameter identification method for two-axis on-road vehicle is presented. The modal parameters of vehicle are identified by using the State Variable Method. To make it possible to determine the matrices M, C, and K of the vehicle, a known mass matrix ΔM is designed to add into the vehicle in order to increase the number of equations ensuring that the number of equations is more than the one of unknowns. Therefore, the physical parameters of vehicle can be estimated by using the least square method. To validate the presented method, a numerical simulation example and an experiment example are given in this paper. The numerical simulation example shows that the largest of absolute value of percentage error is 1.493%. In the experiment example, a school bus is employed in study for the parameter identification. The simulation result from full-car model with the estimated physical parameters is compared with the test result. The agreement between the simulation and the test proves the effectiveness of the proposed estimation method.